2009
DOI: 10.1002/stem.189
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of Functional Retinal Pigmented Epithelium from Induced Pluripotent Stem Cells

Abstract: Human induced pluripotent stem cells (iPSCs) have great promise for cellular therapy, but it is unclear if they have the same potential as human embryonic stem cells (hESCs) to differentiate into specialized cell types. Ocular cells such as the retinal pigmented epithelium (RPE) are of particular interest because they could be used to treat degenerative eye diseases, including age-related macular degeneration and retinitis pigmentosa. We show here that iPSCs generated using Oct4, Sox2, Nanog, and Lin28 can spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
308
1
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 386 publications
(330 citation statements)
references
References 58 publications
16
308
1
5
Order By: Relevance
“…iPSCs can be directed to a variety of lineages, including RSCs and RPESCs. iPSC-derived RPE-like cells (iPSC-RPEs) [67][68][69][70] transplanted into the retina show incorporation into the photoreceptor layer with rescue of vision in an animal model [71]. RSCs have also been derived from iPSCs by selecting retinal rosettes [68] or by directing differentiation with small molecules [72].…”
Section: Pluripotent Stem Cellsmentioning
confidence: 99%
“…iPSCs can be directed to a variety of lineages, including RSCs and RPESCs. iPSC-derived RPE-like cells (iPSC-RPEs) [67][68][69][70] transplanted into the retina show incorporation into the photoreceptor layer with rescue of vision in an animal model [71]. RSCs have also been derived from iPSCs by selecting retinal rosettes [68] or by directing differentiation with small molecules [72].…”
Section: Pluripotent Stem Cellsmentioning
confidence: 99%
“…Production of RPE cells from ESC and iPSC has been established by a number of different laboratories that have developed protocols for generation of homogeneous polarized RPE monolayer cultures. 12,45,46,47 iPSC-derived RPE cells can be isolated, expanded, differentiated, reseeded, and monitored both for morphology and functionality. 48 Also highly significant has been the discovery that iPSC/ ESC are able to self-assemble into three-dimensional (3D) optic cup structures, which then form stratified neural retinal tissues.…”
Section: Retinal Differentiation Of Ipscmentioning
confidence: 99%
“…While the reported survival rates of implanted RPE in the subretinal space of RCS rats and mice vary greatly, there is potential for them to survive for several months or years 9,10,12,20 . RPE cells can be obtained in sufficient numbers for transplantation by deriving them from pluripotent stem cells [9][10][11][12][13][14][25][26][27][28] . Several independent groups have demonstrated that these cells function in similar ways to their somatic counterparts, and long term studies suggest that they are safe upon implantation in rat and mouse disease models 9,10,12,14,19,20,25,[29][30][31][32] .…”
Section: Introductionmentioning
confidence: 99%
“…RPE cells can be obtained in sufficient numbers for transplantation by deriving them from pluripotent stem cells [9][10][11][12][13][14][25][26][27][28] . Several independent groups have demonstrated that these cells function in similar ways to their somatic counterparts, and long term studies suggest that they are safe upon implantation in rat and mouse disease models 9,10,12,14,19,20,25,[29][30][31][32] . The use of induced pluripotent stem cells instead of embryonic stem cells may be advantageous since ethical issues and immunological challenges associated with allogeneic RPE may be obviated 33,34 .…”
Section: Introductionmentioning
confidence: 99%